An assessment of the impact of illegal artisanal gold mining on the environment in parts of Chewore Safari Area, Northern Zimbabwe - Jeremiah Chakuya; Norman Munkuli; Courage Mutema; Edson Gandiwa (Environmental Research Communications, 2023)
Illegal artisanal gold mining threatens biodiversity conservation within protected areas. The objectives of this study were to: (i) assess the environmental impacts of illegal artisanal gold mining in Chewore Safari Area (CSA) and (ii) assess trends in illegal artisanal gold mining within CSA, northern Zimbabwe. A mixed methods approach was used to collect data (i) from law enforcement records kept at CSA focusing on the period 2014 to 2021, and (ii) from field visits to areas affected by illegal artisanal gold mining. The study found that there was a gold rush into CSA with many people from the adjacent communities being arrested and prosecuted in the year 2014. A gradual decline trend in illegal gold mining activities was observed. Equipment or tools were confiscated from illegal miners including gold metal detectors. Site observations indicated destructive gold mining practices associated with visible land degradation. The study recommended increased law enforcement and awareness programmes within communities adjacent to CSA and reclamation of mined sites.